a Upaya Mengkatkan Kreatifitas Melalui Media Pembelajaran Mozaik Gambar Untuk Melatih Motorik Anak Usia Dini Di Desa Kebanggan - Kusuma, Indah; Salmia, Umi; Nurfadila, Maulida; Na'amah, Ulum; Azizah, Muwafaqoh; Adinugraha, Hendri Hermawan (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2024)
This article contains issues regarding the effors to increase creativity through picture mosaic learning media to train early chidhood motor skills in prede village. In this case, not only the teacher plays a role, but parents and the community also contribute to increasing children's creativity through mosaic activities. The objectives of the activity are: 1 child understand the art of mosaics, 2. The writer is able to provide stimulation for the development of artistic potential in children, 3. Children understand the design of a picture mosaic art work 4. Children acquire skills about the art of picture mosaics. The target of this community service activity is relatives in the village where the Community Service Program is located. The method of this service activity is in the form of qualitative and training for children in the village, which consists of 3 stages of activity, namely: 1. The preparation stage, 2. The training implementation stage, and 3. The post-training stage. The training methods used in this service are: lectures, questions and answers, practice, and simulations. The results achieved are: 1). As many as 2 groups received 4–5 star history with very good criteria, 2). As many as 2 groups got complicated 3-2 with good criteria, 3) Almost all children understood the concept of art by drawing mosaics, 4). Children are able to develop teaching materials and are able to make works of art sticking to mosaics on pictures, with the criteria of being independent, creative, neat, correct technique, and good color aesthetics and themes.